PENERAPAN DASA DARMA BAGI ANGGOTA PRAMUKA DALAM KEHIDUPAN SEHARI-HARI DI GUDEP 08001-08002 UNIVERSITAS RIAU KOTA PEKANBARU - Haminiati, Rena Haminiati; Maemunaty, Titi Maemunaty; Baheram, Murni Baheram (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Formulation of the problem in this study is whether the application of Ten Dasa Darma For Scouts Members in Everyday Life in Gudep 08001-08002 Pekanbaru City Riau University already relatively high. The purpose of this study is determine the level of Application of Dasa Darma For Scouts Members in Everyday Life in Gudep 08001-08002 Pekanbaru City Riau University. The benefits of this research can add insight into the application of dasa darma scout in everyday life. This is a descriptive study with a quantitative approach. The population is 30 people. The samples in this study used random sampling. The instrument used in this study was a questionnaire containing 64 items statement, Dasa Dharma Application For Scouts Members in Everyday Life in Gudep 08001-08002 Pekanbaru, Riau University City, with indicator 1) Piety To God Almighty, 2) Love Natural and dear Humans 3) Patriot Polite and Knights, 4) Obey and deliberative, 5) Helpfull Rela and Steadfast, 6) Diligent, Skilled, and Happy, 7) Save, Accurate, and Unpretentious, 8) Discipline, Deredevil, and Loyalty, 9) Responsible and Trustworthy, 10) in the Holy Thoughts, Words and Deeds. From the research result shows that the adoption of Dasa Darma For Scouts Members in Everyday Life in Gudep 08001-08002 Pekanbaru City Riau University referred to in this study are members of scout who follows the scouts in the high category. Key Word: Application, Dasa Darma, Scouts.